2015
DOI: 10.1002/2015gl066681
|View full text |Cite
|
Sign up to set email alerts
|

Dolomite abundance in Chinese loess deposits: A new proxy of monsoon precipitation intensity

Abstract: Dolomite of detrital origin in carbonate‐rich soil can help indicate the intensity of carbonate dissolution and leaching processes. Using Fourier transform infrared spectroscopy, we generated a high‐resolution record of dolomite and calcite contents from eight sections on the Chinese Loess Plateau spanning the last 130 kyr. Based on the relative abundance of calcite and dolomite, four dissolution phases of carbonate minerals related to summer monsoon (SM) variations are identified as follows: (1) coexistence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 51 publications
1
46
1
Order By: Relevance
“…During the weakly weathered substages (Marine Isotope Stages (MIS) 5 b and d) in the last interglacial, the dolomite and total carbonate contents are close to those in the last glacial period (Figure ) in the western Jingyan section (Meng et al, ), which is a very weak weathered period also supported by low magnetic susceptibility (Meng et al, ) and high δ 13 C of bulk carbonate (Sun et al, ; Sun et al, ). This suggests that the initial total carbonate and dolomite content is generally constant during the glacial‐interglacial cycles (Meng et al, ), which is indicated by uranium comminution age (Li et al, ), Sr‐Nd isotopic compositions (Wang et al, ; Zhang et al, ), and high‐resolution age spectra of detrital zircons (Fenn et al, ). For the Pleistocene epoch, the mean total carbonate content in the loess layers of the LC section (Meng et al, ) is close to its average value of the last glacial in the six sections (Figure ).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…During the weakly weathered substages (Marine Isotope Stages (MIS) 5 b and d) in the last interglacial, the dolomite and total carbonate contents are close to those in the last glacial period (Figure ) in the western Jingyan section (Meng et al, ), which is a very weak weathered period also supported by low magnetic susceptibility (Meng et al, ) and high δ 13 C of bulk carbonate (Sun et al, ; Sun et al, ). This suggests that the initial total carbonate and dolomite content is generally constant during the glacial‐interglacial cycles (Meng et al, ), which is indicated by uranium comminution age (Li et al, ), Sr‐Nd isotopic compositions (Wang et al, ; Zhang et al, ), and high‐resolution age spectra of detrital zircons (Fenn et al, ). For the Pleistocene epoch, the mean total carbonate content in the loess layers of the LC section (Meng et al, ) is close to its average value of the last glacial in the six sections (Figure ).…”
Section: Discussionmentioning
confidence: 86%
“…Typical samples were dry sieved to obtain the <63‐μm (similar to the loess grain size range; Yang & Ding, ), 63‐ to 150‐, and >150‐μm fractions in order to evaluate carbonate distribution in the fine‐ and coarse‐grained fractions. For loess samples, the last glacial Jingtai section (37.46°N, 103.79°E) was sampled, and carbonate investigations were performed by Meng et al () in additional five sections (Figure ) over the last glacial cycles across the CLP, including Jingyan, Huanxian, Pingliang, Xifeng, and Luochuan (LC) sections as well as Pleistocene loess units (glacials) in the LC section referred to in Meng et al (; Figure ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dust carried by wind has a similar mineral composition to its source, but the minerals exposed to atmosphere undergo physical or chemical weathering due to thermodynamic instability (Liu, 1985;Balsam et al, 2004;Ji et al, 2001Ji et al, , 2009Meng et al, 2015). Calcite can be both primary (i.e.…”
Section: Paleoenvironmental Significance Of Mineralsmentioning
confidence: 99%